Teachers’ instructional practices in teaching english at Malaysian primary schools - Othman, J. (2010)
Recent trends in Malaysian’s educational policy have focused on meeting the challenges of globalization and internationalization. As English has achieved the status of a major international language, the government of Malaysia has been actively expanding the teaching of English as an essential part of the school curriculum. The issue of how to improve the standard of English proficiency among young learners has been one of the most discussed in Malaysia. Learning English, as envisaged in the ELT curriculum, should be fun and pupil-centred. As part of an effort to examine the state of ELT in Malaysian primary schools, this study looked at the instructional strategies employed by English language teachers in their classrooms. A survey was conducted in six states in Malaysia which represent the northern region, east and west coast of the peninsula and East Malaysia. The sample comprised of 215 English teachers teaching at primary level. The findings of this study revealed that English language teaching practices employed by primary school teachers in Malaysia were in line with the English curriculum stipulated by the Ministry of Education. Data indicated that teachers employed teaching strategies which are learner-centred, interactive, develop oracy and literacy skills. Furthermore, the results also indicated that the teachers’ instructional practices are closely related to their teaching experience.